Outgroup residents attitude towards the existence of special Islamic housing - Hendro Prabowo; Mahargyantari P Dewi; Henny Regina Salve; Afmi Fuad (Universitas Ahmad Dahlan, 2019)
A gated community is a gated residential area its mean as a term with a negative connotation related to social segregation. Today there has also been a growing upper-class housing that is devoted to Muslims in Jakarta. One of them is Light Islamic Townhouse in East Jakarta. This case study examines the attitude of the out-group resident to the housing, where the out-group resident is the same neighborhood with the resident of the housing (living in the same Rukun Tetangga). With interviewed to 16 participants and did participant observation, the results show that middle class from the out-group resident consider the existence of the housing as closed, unwilling to blend, and exclusive. While the lower class from the out-group resident considered the existence of the housing to be positive and profitable because of cross-subsidies. Practical and theoretical implications are discussed.Â Keywords: attitude, out-group, gated community.